Drivers of Customer Loyalty towards Islamic Subsidiary Banks in the Northern States of Peninsular Malaysia - Abdul Rahman, Maria; Fairuz Ramli, Mona (International Journal of Engineering and Technology, 2018)
It is undeniable that customer loyalty contributes to the sustainability and success of the banking industry. With the intense competition in the industry, banks are now trying to retain their customers with the aim to increase their revenues. As there are disagreements among the variables that influence customer loyalty, this study examined the relationships between perceived value, image, satisfaction and loyalty in an integrative model. Analysis was done on data collected from 139 bank customers in the northern states of Peninsular Malaysia using Partial Least Squares. The results of the study revealed that perceived value and bank image led customers to experience greater satisfaction, resulting in customers to be more loyal to their banks. The research outcome contributes to the body of knowledge by integrating the four variables into one model and by testing the model in the banking industry. The findings from this study may assist bank managers to formulate strategies to increase their revenues through customer loyalty.Â Â Â